El Conde de Galarza y el método crítico en la enseñanza de la filosofía - Abd al Halîm Atiyya, Ahmad (Anales del Seminario de Historia de la Filosofía, 2003)
In 1908, public figures of the Egyptian civil society created the Egyptia University on the pattern of European universities. Foreign scholars belonged to its faculty including orientalists. The only Spaniard appointed as professor was Vicente Galarza y Pérez Castañeda, who taught philosophy in the years between 1915 and 1919. The article analyses the texts of his courses, taught in Arabic, and considers Galarza to be the first to apply the critical method in his university teaching.